Production of Single Cell Protein from Underutilized Sea Weed Turbinaria Spp Using Mixed Culture of Palmyrah Toddy - Shayanthavi, S.; Kapilan, R. (University of Jaffna, 2020)
Due to the steep increasing global population, the demand for protein increases day by day. To overcome the protein shortage, single cell protein (SCP) is used as a protein supplement for human and animals. This study was aimed to produce SCP from the extracts of underutilized, abundantly found marine sea weed, Turbinaria spp as the substrate, using the mixed culture of organisms grown in palmyrah (Borassus flabellifer) toddy. Turbinaria spp were collected, sundried, ground to a powder form and Turbinaria solution was prepared by mixing distilled water and this was used as a growth medium throughout the experiment without adding any supplements. This medium [10 g Turbinaria spp powder in 100 mL water (10% w/v)] was inoculated with 10 mL natural palmyrah toddy and allowed to submerged fermentation at 29 °C for 72 h which yielded a crude protein of 38.5% (w/v). When the growth temperature was optimized at 35 °C (43.4%), SCP yield was significantly increased by 1.36 times than the initial non- optimized temperature 27 °C (32.7%). When fermentation period was optimized as 48 h (44.33%), SCP yield was significantly increased by 1.14 times than the initial non- optimized time (24 h-38.55%). Turbinaria spp medium and inoculum ratio was optimized as 50:10 (43.7%), for higher SCP yield. When initial pH of the medium was set at 6.0, significantly higher relative SCP was produced. Amino acid analysis revealed that the SCP produced in the Turbinaria medium had all the essential amino acids with significantly higher amount of methionine (3.9%) and lower amount of threonine (0.2%). Vitamin B analysis revealed that SCP yield in the Turbinaria medium contained thiamin (0.85 mg/100g) and riboflavin (3.2 mg/100g). After the optimization of growing conditions and media composition, SCP production in the medium containing under-utilized sea weed Turbinaria, increased by 1.13 times (from 38.5% to 43.7%).
Keywords: Crude protein; Submerged fermentation; Single Cell Protein; Turbinaria